ANALISIS PERMINTAAN PANGAN RUMAH TANGGA PENERIMA MANFAAT BANTUAN PANGAN NON TUNAI (BPNT) DI KOTA BOGOR - Anisah Nasution; Bayu Krisnamurthi; Dwi Rachmina (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2020)
Food is a basic need and access to food is a human rights that must be fulfilled. Meeting food needs is the main target of food policy carried out by the government, especially for the poor household. One of the government's policies in terms of food is Non-Cash Food Assistance (BPNT). The purpose of this study was to analysis the food demand for BPNT's beneficiary household and not receiving BPNT. This study used primary data on food consumption with the highest share of expenditure of poor households in Bogor City. Demand for food was estimated by LA-AIDS (Linear Approximation Almost Ideal Demand System) model. The results this study showed that there were significant differences in the average consumption of rice, non-rice and animal protein consumption between BPNT and non-BPNT households. The highest of food expenditure in both households was processed food and beverages. The BPNT dummy variable did not sign for a share of food expenditure. The result of the estimate also showed that rice, animal protein, vegetables, food and beverages and cigarettes are inelastic at their prices elasticity. All types of food studied were normal goods. Non-rice, vegetables and processed food and beverages were substitutes for rice in BPNT recipient households while in non-BPNT only processed food and beverages was substitutes for rice. The interesting thing in this research was that cigarettes become a complimentary item to all foods.